The EU promotion of Human Rights in Central Asia - Shakenova, A.; Kassymova, A.; Zhumadildayeva, A. ("M. Narikbayev KAZGUU University". Nur-Sultan, 2020)
Central Asian countries became part of international community after the fall of the Soviet Union. European Union is one of international actors building presence in Central Asia. This research paper explores the main aspects of EU promotion of human rights in Central Asia. It aims to analyze the EU’s self-conception through discourse as an external actor, the instruments and strategies applied to promote human rights by the EU, factors that impede the development of relations between Central Asia and EU that lead to a low impact of the EU’s assistance, and the reception of its action in Central Asia. It investigates some specific cases where human rights have been violated in Kazakhstan and where the EU has been involved. The research paper concludes that despite the contribution of EU to regional security, spread of democracy and observance of human rights in Central Asia, all these efforts will become futile if nothing is changed on the intraregional level which includes better domestic governance of Central Asian states, commitment to democracy and lower corruption. EU can be considered as a deterrent for Central Asian governments against violation of democratic principles and human rights.
Keywords: EU as a global actor, EU in Central Asia, Human Rights in Central Asia